2018
DOI: 10.1021/acs.molpharmaceut.7b01091
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid-Based Drug Delivery Systems for Enhanced Doxorubicin Encapsulation: Comparing Hydrophobic and Ionic Interactions in Drug Loading and Release

Abstract: Doxorubicin (Dox) is a drug of choice in the design of drug delivery systems directed toward breast cancers, but is often limited by loading and control over its release from polymer micelles. Bile acid-based block copolymers present certain advantages over traditional polymer-based systems for drug delivery purposes, since they can enable a higher drug loading via the formation of a reservoir through their aggregation process. In this study, hydrophobic and electrostatic interactions are compared for their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 63 publications
(137 reference statements)
1
34
0
Order By: Relevance
“…Foreign hydrophobic molecules or NPs are harmful to biological systems by disrupting cell membrane and protein folding. On the other hand, a certain degree of hydrophobicity was needed for drugs to cross cell membranes or biological barriers (Cunningham et al, 2018). Protein corona formation may change the hydrophobicity of NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Foreign hydrophobic molecules or NPs are harmful to biological systems by disrupting cell membrane and protein folding. On the other hand, a certain degree of hydrophobicity was needed for drugs to cross cell membranes or biological barriers (Cunningham et al, 2018). Protein corona formation may change the hydrophobicity of NPs.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the hydrophilic, long-retention/stealth effect, and biocompatibility, polyethylene glycol (PEG) was often introduced to steroid scaffolds [72]. In fact, PEGylated bile acids were synthesized to further prepare self-emulsifying drug delivery systems (SEDDSs), which could enhance the solubility and absorption of poor water-soluble antitumor agent (doxorubicin [73]) or antibiotics (itraconazole [74]), thus providing a significant enhancement of solubility and bioavailability of these small molecular drugs. The emulsions consisted of spherical micelles with a mean hydrodynamic diameter around 100-220 nm, with good biocompatibility (low cytotoxic and hemolytic effect).…”
Section: Steroid-based Supramolecular System For Small Molecule/drug mentioning
confidence: 99%
“…Zhu and co-workers reported the synthesis of series polymers based on CA, and using them in drug delivery systems. Research indicated that the micelles formed from cholic acid-based star polymers had a lower density than linear polymers with a similar structure, forming an internal reservoir that can accommodate a larger amount of hydrophobic therapeutic drug, showing their advantages in terms of biocompatibility and drug loading [31,32,33,34,35]. The drug loading and encapsulation efficiency of these nanoparticles reached up to 35 wt % and higher than 89%, respectively, improving bioavailability and pharmacokinetics of the drug.…”
Section: Introductionmentioning
confidence: 99%